2018
DOI: 10.1038/s41419-018-0385-4
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing IL-36-driven inflammation using peptide pseudosubstrates for neutrophil proteases

Abstract: Sterile inflammation is initiated by molecules released from necrotic cells, called damage-associated molecular patterns (DAMPs). Members of the extended IL-1 cytokine family are important DAMPs, are typically only released through necrosis, and require limited proteolytic processing for activation. The IL-1 family cytokines, IL-36α, IL-36β, and IL-36γ, are expressed as inactive precursors and have been implicated as key initiators of psoriatic-type skin inflammation. We have recently found that IL-36 family c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 62 publications
(72 reference statements)
0
34
0
Order By: Relevance
“…In the attempt to develop additional strategies to target the activation of the IL-36 cytokines, small molecules inhibiting the elastase have been generated. Since their efficacy to reduce IL-36 activation has been proven [80], they might represent a novel approach to inhibit IL-36-driven inflammation in psoriasis and other IL-36-dependent inflammatory diseases [81].…”
Section: Expression and Role Of Il-36 Cytokines In Inflamed Skin Amentioning
confidence: 99%
“…In the attempt to develop additional strategies to target the activation of the IL-36 cytokines, small molecules inhibiting the elastase have been generated. Since their efficacy to reduce IL-36 activation has been proven [80], they might represent a novel approach to inhibit IL-36-driven inflammation in psoriasis and other IL-36-dependent inflammatory diseases [81].…”
Section: Expression and Role Of Il-36 Cytokines In Inflamed Skin Amentioning
confidence: 99%
“…As an IL-36R agonist, IL-36γ is now considered to be a valuable biomarker in psoriatic patients, which correlates closely with disease activity 8. Similar to IL-36α and IL-36β, IL-36γ is expressed as an inactive precursor, which needs to be proteolytically processed and activated, and neutrophil-derived proteases seemed to be potent activating enzymes of IL-36γ 9. Henry et al reported neutrophil elastase (NE) could cleave recombinant full-length (FL)-IL-36γ and activate the protein;10 however, Johnston et al found cathepsin G (CG) but not NE had the ability to activate IL-36γ in vitro, and NE could cleave FL-IL-36α 2…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, peptide-based pseudosubstrates for Cathepsin G and elastase were developed. These substrates can decrease the activated interleukin-36 (IL-36) family cytokines especially in case of inflammatory diseases(e.g., psoriasis, arthritis)because such cytokines are proteolytically processed in the presence of Cathepsin G and other proteases [191]. In another study, it was proven that amodiaquine, an antimalarial drug, inhibited host Cathepsin B to protect host cells against infection with multiple toxins or viruses [192].…”
Section: Miscellaneousmentioning
confidence: 99%